The Slang Words from Turning Red Movie Script - Shan Derwin Susanto; Luh Putu Laksminy; Ni Luh Putu Krisnawati (Jurnal Langua, 2023)
This study examines the types and functions of slang words in the movie script of "Turning Red," a comedic and fantastical animated film released in 2022. Slang, as an informal and dynamic form of language, plays a significant role in contemporary socialization and communication among young people. The research draws on sociolinguistic perspectives to explore the different categories and functions of slang words in the movie script. The analysis was conducted based on the theories proposed by Allan & Burridge (2006). The findings of the analysis reveal various types of slang words used in the movie script, including fresh and creative, flippant, imitative, acronym, and clipping types. The collected data is analyzed by using the descriptive qualitative method since it did not involve any numerical data. This study contributes to the understanding of slang as a sociolinguistic phenomenon and its significance in contemporary media, specifically in movie scripts. By examining the types and functions of slang words in "Turning Red," the research provides insights into the linguistic choices made by the filmmakers to reflect the experiences and language use of young people. The findings enhance our understanding of how slang contributes to the portrayal of social and cultural aspects in movies, highlighting its impact on society and language evolution. The study also examines the sociolinguistic functions of slang in the movie, shedding light on its role in expressing identity, fostering social connections, and reflecting contemporary youth culture.